Gastronomía típica y la calidad del servicio en la ciudad de Babahoyo - Viscarra Icaza, Cinthya Elizabeth (2019)
This Research Project is oriented to the Typical Gastronomy and Service Quality of the City of Babahoyo, it could be located within the Cultural Tourism of the Province of Los Ríos. Located in the Coastal or Coast Region, located in the center of the country, and named for the presence of existing hydrographic tributaries throughout its territory, it is evident from its Pre-Columbian origins the existence of archaeological vestiges of this coastal culture considered one of the oldest on the Ecuadorian coast as is the Chorrera Culture that belongs to the Formative Period and is located in the period from 1550-500 BC Archaeological remains of the Valdivia, Tejar-Daule and Milagro-Quevedo cultures have also been found. (P. Pedro I. Porras, 2016) Being discovered by the Ecuadorian archaeologist and historian Don Francisco Huerta Rendón "The Chorrera phase is of special importance because it is the first one to settle definitively in the Guayas basin, close to the dissemination routes to the mountains and then to the east" According to the historical data of the anthropologist and sociologist Carlos Betemberg and Platzaert, the foundation of the city of Santa Rita de Babahoyo is established, also known as "bodegas". This is the place where the royal customs worked and all the products coming from the Ecuadorian coast and sierra, serving as transit for the commerce of said merchandise.